Evaluation Of Joint Motion : Methods of Measurement and Recording - Esch, Dortha (Book collections on Project MUSE., 1970)
A manual for use either in teaching or in clinical practice in occupational and physical therapy, prosthetics, orthotics, and related medical fields.